The Association Between the Quality of Care Provided by Family Members and the Quality of Their Relationship With the Care Receiver in Dementia: A Mixed-methods Observational Study - Chiara Carparelli PhD; Jan R. Oyebode PhD; Gerard A. Riley PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Research suggests that the quality of care provided by family members may be influenced by the quality of relationship they have with the person living with dementia. The study investigated this in the context of assisting with daily activities. The quality of the relationship was assessed using the conceptual framework of relationship continuity/discontinuity which focuses on whether the carer experiences their relationship as continuous or discontinuous with the pre-dementia relationship. Thirty spousal carers completed the Birmingham Relationship Continuity Measure . Participants were also interviewed about how they provide care for their partner’s daily activities. Passages consistent with a more person-centered approach were identified, and the total number of these in each transcript was used as the measure of care quality. There was a significant correlation between questionnaire scores and the number of person-centered passages: Those reporting greater continuity more frequently described using a person-centered approach. Findings were consistent with earlier research suggesting associations between the quality of the relationship and the quality of care. The concept of relationship continuity suggests ways in which relationship and care quality are connected, and these suggestions could be used to develop interventions to help family carers provide better care.